Peran Dewan Komisaris Dalam Memoderasi Pengaruh Intellectual Capital Disclosure Terhadap Nilai Perusahaan - Chen, Ming (Jurnal Keuangan dan Bisnis, 2021)
The purpose of this study is to test empirically whether the size of the board of commissioners can moderate the broad relationship of intellectual capital disclousure to firm value. In this study, the size of board of commissioners is measured by the nymber of commissioners is measured by the number of commissioners in the company. Intellectual capital dislosure is measured by the ICD Index which consists of 25 items. Meanwhil, the company value uses price book value. The sample of this research is banking companies listed on the Indonesia Stock Exchange from 2016 to 2020. This study uses the MRA model and uses SPSS as a testing tool